The expression of a viral microRNA is regulated by clustering to allow optimal B cell transformation - Haar, Janina; Bernhardt, Katharina; Feederle, Regina; Diederichs, Sven; Delecluse, Henri-Jacques (Nucleic acids research, 2016)
Abstract. The Epstein-Barr virus (EBV) transforms B cells by expressing latent proteins and the BHRF1 microRNA cluster. MiR-BHRF1-3, its most transforming memb